Microbial inoculation of seed for improved crop performance: issues and opportunities - O’Callaghan, Maureen (Appl Microbiol Biotechnol, 2016)
There is increasing interest in the use of beneficial microorganisms as alternatives to chemical pesticides and synthetic fertilisers in agricultural production. Application of beneficial microorganisms to seeds is an efficient mechanism for placement of microbial inocula into soil where they will be well positioned to colonise seedling roots and protect against soil-borne diseases and pests. However, despite the long history of inoculation of legume seeds with Rhizobia spp. and clear laboratory demonstration of the ability of a wide range of other beneficial microorganisms to improve crop performance, there are still very few commercially available microbial seed inoculants. Seed inoculation techniques used for research purposes are often not feasible at a commercial scale and there are significant technical challenges in maintaining viable microbial inocula on seed throughout commercial seed treatment processes and storage. Further research is needed before the benefits of a wide range of environmentally sensitive potential seed inoculants can be captured for use in agriculture, ecosystem restoration and bioremediation. There is no single solution to the challenge of improving the ability of seed inoculants to establish and function consistently in the field. Development of novel formulations that maintain the viability of both inoculant and seed during storage will result from multidisciplinary research in microbial and seed physiology and adjuvant chemistry.